Beyond single support calls: Efficacy of follow-up callbacks for dementia caregivers using the Alzheimer’s association helpline - Nancy A. Hodgson; Sonia Talwar; Subhash Aryal; Kerry Finegan; Sam Fazio (PLoS ONE, 2025)
Background Family care partners of persons living with dementia (PLWD) have limited support and resources and experience high levels of stress and burden. Prior research has demonstrated that one call to the Alzheimer’s Association’s Helpline benefitted 80% of callers following a single call. However, some care partners need more support than a single call. The aim of this study was to evaluate the efficacy of offering up to two additional Helpline care consultations after an initial call to the Helpline. Methods 2503 study participants were Helpline callers who received one, two, or three care consultations at the callers’ request. The PROMIS measure of self-efficacy in managing emotions was assessed among participants over time (baseline to two weeks after each care consultation), and differences were assessed between caller groups. Results No statistical differences were noted in demographics between those who received a single call versus two or three calls. Baseline self-efficacy scores were significantly lower in those who requested more than one call (p < 0.01). Self-efficacy scores improved over time in all three groups of callers, and the improvement was significant in those who received one and two care consultations (p < 0.01). Conclusions Further research is indicated to understand the specific support needs of care partners that can benefit from more than one call to a telesupport helpline.